Genetic variation among Jatropha curcas L. using dominant molecular marker collected from different agro-climatic regions of India - Kole, Pravas Ranjan; Bhat, K.V.; Chaudhary, Rekha; Malik, S.K. (The Indian Journal of Genetics and Plant Breeding, 2016)
Genetic variability and relationship among 182 accessions of Jatropha curcas collected from total 19 Indian states were analysed based on random amplified polymorphic DNA (RAPD) marker. A total of 30 primers were chosen which produced 263 bands of which 254 were polymorphic (96.82%) across the studied accessions.The polymorphic information content (PIC) was highest for the primer Oligo 905 (0.901) and the lowest was OPAD 11 (0.620) with an average of 0.791. Jaccard’s coefficient of similarity varied from 0.31 to 0.98 indicates the high level of genetic variation among the genotypes studied.The overall grouping pattern of clustering corresponds well with the principal component analysis (PCA), confirming patterns of genetic diversity observed among the accessions.